Defective Glucagon Secretion During Hypoglycemia After Intrahepatic But Not Nonhepatic Islet Autotransplantation. Issue 8 (8th July 2014) - Bellin, M. D.; Parazzoli, S.; Oseid, E.; Bogachus, L. D.; Schuetz, C.; Patti, M. E.; Dunn, T.; Pruett, T.; Balamurugan, A. N.; Hering, B.; Beilman, G.; Sutherland, D. E. R.; et al.
<x xml:space="preserve">Abstract</x> Defective glucagon secretion during hypoglycemia after islet transplantation has been reported in animals and humans with type 1 diabetes. To ascertain whether this is true of islets from nondiabetic humans, subjects with autoislet transplantation in the intrahepatic site only (TP/IAT‐H) or in intrahepatic plus nonhepatic (TP/IAT‐H+NH) sites were studied. Glucagon responses were examined during stepped hypoglycemic clamps. Glucagon and symptom responses during hypoglycemia were virtually absent in subjects who received islets in the hepatic site only (glucagon increment over baseline = 1 ± 6, pg/mL, mean ± SE, n = 9, p = ns; symptom score = 1 ± 1, p = ns). When islets were transplanted in both intrahepatic + nonhepatic sites, glucagon and symptom responses were not significantly different than Control Subjects (TP/IAT‐H + NH: glucagon increment = 54 ± 14, n = 5; symptom score = 7 ± 3; control glucagon increment = 67 ± 15, n = 5; symptom score = 8 ± 1). In contrast, glucagon responses to intravenous arginine were present in TP/IAT‐H recipients (TP/IAT: glucagon response = 37 ± 8, n = 7). Transplantation of a portion of the islets into a nonhepatic site should be seriously considered in TP/IAT to avoid posttransplant abnormalities in glucagon and symptom responses to hypoglycemia.